Design, synthesis, and cytotoxic activity of novel 7-substituted camptothecin derivatives incorporating piperazinyl-sulfonylamidine moieties. Issue 17 (1st September 2017) - Yang, Cheng-Jie; Song, Zi-Long; Goto, Masuo; Liu, Ying-Qian; Hsieh, Kan-Yen; Morris-Natschke, Susan L.; Zhao, Yong-Long; Zhang, Jun-Xiang; Lee, Kuo-Hsiung
Graphical abstract: Abstract: In our continuing search for camptothecin (CPT)-derived antitumor drugs, novel 7-substituted CPT derivatives incorporating piperazinyl-sulfonylamidine moieties were designed, synthesized and evaluated for cytotoxicity against five tumor cell lines (A-549, MDA-MB-231, MCF-7, KB, and KB-VIN). All of the derivatives showed promising in vitro cytotoxic activity against the tested tumor cell lines, and were more potent than irinotecan. Remarkably, most of the compounds exhibited comparable cytotoxicity against the multidrug-resistant (MDR) KB-VIN and parental KB tumor cell lines, while irinotecan lost activity completely against KB-VIN. Especially, compounds13r and13p (IC50 0.38 and 0.85 μM, respectively) displayed the greatest cytotoxicity against the MDR KB-VIN cell line and merit further development into preclinical and clinical drug candidates for treating cancer, including MDR phenotype.